The efficacy and safety of add-on 0.1% brimonidine tartrate preserved with sodium chlorite in on-treatment Japanese normal-tension glaucoma patients - Tsumura T (Dove Medical Press, 2014)
Toyoaki Tsumura,1 Keiji Yoshikawa,2 Tairo Kimura,3 Hirotaka Suzumura,4 Miwako Kawashima,5 Mami Nanno,6 Kiyotaka Ishijima,7 Ryuji Takeda8 1Fussa Hospital, Tokyo, Japan; 2Yoshikawa Eye Clinic, Tokyo, Japan; 3Ueno Eye Clinic, Tokyo, Japan; 4Suzumura Eye Clinic, Tokyo, Japan; 5Nakano General Hospital, Tokyo, Japan; 6Kagurazaka Minamino Eye Clinic, Tokyo, Japan; 7Irumagawa Hospital, Saitama, Japan; 8Department of Biological Chemistry, Faculty of Agriculture, Kinki University, Nara, Japan Background: To evaluate the efficacy and safety of newly formulated brimonidine (0.1% brimonidine tartrate preserved with sodium chlorite: brimonidine) as add-on therapy in on-treatment Japanese normal-tension glaucoma (NTG) patients.Methods: Brimonidine was added to on-treatment NTG patients with intraocular pressures (IOP) of between 13 mmHg and 16 mmHg after three consecutive IOP measurements. The time courses of IOP, conjunctival hyperemia, superficial punctate keratitis, and adverse events were examined at 4, 8, and 12 weeks after brimonidine instillation.Results: Though 75 of 83 patients (31 males and 52 females; mean age: 63.4±11.6 years) completed the study, six patients discontinued because of side effects and two patients withdrew. The mean IOP after brimonidine addition at week 4 (12.6±1.8 mmHg, P<0.001), week 8 (12.4±1.7 mmHg, P<0.001), and week 12 (12.6±1.8 mmHg, P<0.001) was significantly decreased compared with that before the addition of brimonidine (13.9±1.2 mmHg). No significant changes in superficial punctate keratitis or conjunctival hyperemia scores were observed throughout the study. Dizziness, sleepiness, eye pain, and itching (mild to moderate) were noted in five, four, three, and three patients, respectively.Conclusions: The addition of newly formulated brimonidine to on-treatment Japanese NTG patients with IOP of 13–16 mmHg further reduced the levels of IOP with minimal side effects and adverse events. Keywords: normal-tension glaucoma, 0.1% brimonidine tartrate with sodium chlorite, additive intraocular pressure reduction, side effect, adverse event